Optimization of biomass production in outdoor tubular photobioreactors. (January 2016) - de Andrade, G.A.; Berenguel, M.; Guzmán, J.L.; Pagano, D.J.; Acién, F.G.
Abstract : Highlights: The microalgal optimization problem of a tubular photobioreactor is discussed. Two different optimization strategies are proposed in this work. Experimental and simulation tests are performed. Abstract: This paper is concerned with microalgal biomass production optimization in outdoor tubular photobioreactors. The main purpose of such optimization system is to calculate the culture medium flow rate in order to maximize the biomass production over a determined period of time. Two different methods are shown in this work: (i) an optimal and (ii) a near-optimal strategy. The optimal strategy belongs to the optimal control theory. In this context, a direct method is used to discretize the control problem and a nonlinear programming technique is applied into the resulting optimization problem. The near-optimal strategy calculates only the culture medium injection time, while the culture medium flow rate is maintained constant during this time. For this aim, a photobioreactor model, under real environmental and culture conditions, is used to compute the injection time. This strategy is mostly important for those photobioreactors that are not equipped with a continuous culture medium valve. Simulation and experimental results allow the user to evaluate the effectiveness of the biomass production optimization strategies proposed in this work, compared with a classical harvesting strategy.